Area 51 Interns: Alien Summer - Book 1 - Murray, James S. (James Stephen), 1976-; Smith, Carsen (New York : Penguin Workshop, 2022)
On the first day of summer vacation twelve-year-old Viv Harlow just wants to relax, but when a whole race of aliens escapes from the famous Area 51 where her mom works, Viv and her friends will have to gear up, work together, and save their parents from alien abduction.
Ages 8-12
Keywords: Escapes -- Juvenile fiction; Cooperativeness -- Juvenile fiction; Extraterrestrial beings -- Juvenile fiction; Escapes -- Fiction; Cooperativeness -- Fiction; Extraterrestrial beings -- Fiction; Preteens -- Fiction; Friendship -- Fiction; Science fiction